Studies in Hellenistic Judaism - Feldman, Louis H. (Arbeiten zur Geschichte des antiken Judentums und des Urchristentums, 1996)
This volume consists of 23 essays that have appeared in 19 different journals and other publications during a period of over 40 years, together with an introduction. The essays deal primarily with the relations between Jews and non-Jews during the period from Alexander the Great to the end of the Roman Empire, in five areas: Josephus; Judaism and Christianity; Latin literature and the Jews; the Romans in Rabbinic literature; and other studies in Hellenistic Judaism. The topics include a programmatic essay comparing Hebraism and Hellenism, pro-Jewish intimations in Apion and in Tacitus, the influence of Josephus on Cotton Mather, Philo's view on music, the relationship between pagan and Christian anti-Semitism, observations on rabbinic reaction to Roman rule, and new light from inscriptions and papyri on Diaspora synagogues.